Sosialisasi Pentingnya Partisipasi Politik Terhadap Gerakan Pemuda GPIB Bukit Zaitun Kota Makassar - Emanuel Omedetho Jermias; Abdul Rahman; Muhammad Syukur; Firman Umar (Institut Teknologi dan Bisnis Semarang, 2023)
For a democratic country like Indonesia, general elections are an arena for citizens to express their political aspirations in the context of national leadership succession which takes place once every five years. General elections are very important for the upholding of democracy. Despite this, there are still citizens who do not exercise their constitutional rights. Therefore, to increase community participation, especially from young voters, this service activity was carried out, by using the GPIB Bukit Zaitun Youth Movement as a partner. The method used is socialization in the form of lectures and discussions. The results of the service received an enthusiastic welcome from the participants and they were committed to exercising their political rights in the upcoming 2024 elections.